CONDITIONS AND FACTORS OF SUCCESSFUL COOPERATION OF RUSSIAN AND FOREIGN UNIVERSITIES - E. Halimon (Вестник университета)
The development of joint programs has become one of the main directions of international cooperation between universities of different countries. Planning international educational programs is a very complex process, as they are closely linked with the economies of countries where universities are situated, with their political, cultural, social and public life. The implementation of such joint programmes contributes to the solution of a number of strategic objectives not only of educational institutions, but of the education sector as a whole. However, it is accompanied by many problems.In this article, the author has identified some conditions that contribute to the formation of mutually beneficial cooperation between educational institutions of Russia and foreign countries, and have detailed the factors that lead to solving current legal problems and strategic challenges in the planning and implementation of joint programs.